A study on nuclei in the SEC - report from the Public Speaking Project in Lund - Mosey, Bryan (HERMES - Journal of Language and Communication in Business, 2017)
As part of the Public Speaking Project in Lund, the Spoken English Corpus has been processed in a number of ways and put into a database format thus allowing the retrieval of accurate statistical data. Based on a simple definition of nucleus provided by Gerry Knowles, the nuclei in the prosodic transcriptions of the material have been located and marked. A field indicating the position of each word within the tone unit (1 representing the last word of the tone unit and 2, the penultimate word etc.) has also been added thus facilitating the statistical study of nucleus position. Also studied are the tone types occurring in the nuclei in the material. Here, the findings provide empirical support for the postulation of a dichotomy of tone types. The functions of the various nucleus types in the text categories making up the material are discussed on the basis of empirical evidence from the material.